Protein Malnutrition Alters Tryptophan and Angiotensin-Converting Enzyme 2 Homeostasis and Adaptive Immune Responses in Human Rotavirus-Infected Gnotobiotic Pigs with Human Infant Fecal Microbiota Transplant - Fischer, David D.; Kandasamy, Sukumar; Paim, Francine C.; Langel, Stephanie N.; Alhamo, Moyasar A.; Shao, Lulu; Chepngeno, Juliet; Miyazaki, Ayako; Huang, Huang-Chi; Kumar, Anand; Rajashekara, Gireesh; Saif, Linda J.; et al. (Clinical and vaccine immunology, 2017)
Malnutrition leads to increased morbidity and is evident in almost half of all deaths in children under the age of 5 years. Mortality due to rotavirus diarrhea is common in developing countries where malnutrition is prevalent; however, the relationship between malnutrition and rotavirus infection remains unclear. In this study, gnotobiotic pigs transplanted with the fecal microbiota of a healthy 2-month-old infant were fed protein-sufficient or -deficient diets and infected with virulent human rotavirus (HRV). After human rotavirus infection, protein-deficient pigs had decreased human rotavirus antibody titers and total IgA concentrations, systemic T helper (CD3 + CD4 + ) and cytotoxic T (CD3 + CD8 + ) lymphocyte frequencies, and serum tryptophan and angiotensin I-converting enzyme 2. Additionally, deficient-diet pigs had impaired tryptophan catabolism postinfection compared with sufficient-diet pigs. Tryptophan supplementation was tested as an intervention in additional groups of fecal microbiota-transplanted, rotavirus-infected, sufficient- and deficient-diet pigs. Tryptophan supplementation increased the frequencies of regulatory (CD4 + or CD8 + CD25 + FoxP3 + ) T cells in pigs on both the sufficient and the deficient diets. These results suggest that a protein-deficient diet impairs activation of the adaptive immune response following HRV infection and alters tryptophan homeostasis.